(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article deals with the problem of implementation of the principle of succes- sion continuity. The philosophical pedagogical origins of continuity in teaching aregiven. The question of the status of the principles of didactics is analyzed where’s in the system of didactics in is proposed to include the principle of continuity in teaching as independent.